IDENTIFIKASI FENOMENA SELF-INCOMPATIBILITY PADA Hibiscus rosa-sinensis L. - Dias Idha Pramesti (LP4MK STKIP PGRI Lubuklinggau, 2021)
Hybridization is one way to produce Hibiscus rosa-sinensis L. which have various shape and colour of flowers. However, this is hampered by the possibility of self-incompatibility in Hibiscus rosa-sinensis L. To identify self-incompatibility in Hibiscus rosa-sinensis L. the simplest methods are used by observing the morphology and anatomy of fruit development, followed by a descriptive analysis of the data that has been obtained. The analysis results on crossing artificial pollination to 103 flowers of single pink Hibiscus rosa-sinensis L. show that the fruits survive until day 7 after pollination. Furthermore, the data show that there is no fruit, seed, and embryo development. Indeed the fruit turns yellow and finally shed. But the self artificial pollination shows that 35 seeds develop from 96 pollinations. The longer seed, which 13 days after pollination, grew up. The globular embryo could find on 3 DAP (day after pollination) fruit set, and the 9 DAP fruit set shows the development of heart shape. The result suggests that the phenomenon of self-incompatibility on Hibiscus rosa sinensis L. predicts as postzygotic self-incompatibility.